Modelling the influence of environmental and weather factors on the density of the invasive polychaete Boccardia proboscidea - Garaffo, Griselda Valeria (2016)
The inter-tidal zone around sewage discharges in a Southwest Atlantic shore (Mar del Plata, Argentina) is currently colonized by extensive inter-tidal reefs of the invasive spionid Boccardia proboscidea. Understanding the links between both human and natural disturbances and the massive development of non-indigenous species will help prevent marine bioinvasions, which are already favoured by global oceanic trade. We present herein predictive models for variations in the density of B. proboscidea around sewage discharges of Mar del Plata, using environmental (pH, turbidity, temperature, salinity and total organic matter content), weather (wind direction and storm records), spatial (sites) and temporal (season and year) variables. Density variations were modelled by generalized linear models, and model averaging (multimodel inference) was used to obtain predicted values. The highest predicted values of B. proboscidea density occurred at sites to the south of the sewage effluent in spring. These sites are more affected by urban effluent discharges and they showed increased B. proboscidea density when the north wind was predominant. In addition, B. proboscidea density values were higher in sites with 20–22 °C (seawater temperature), high total organic matter content in sediments and low salinity. The averaged model was only a good ‘predictive model’ for sites to the north of the outfall, but was useful as an ‘explanatory model’ in all sites. Such predictions may help to back up conservation and management policies and decisions.